1994
DOI: 10.1002/aja.1002010205
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐α and embryonic mouse lung morphogenesis

Abstract: The ontogeny of the embryonic and fetal lung involves complex interactions between epithelial and mesenchymal primordia which require a specific program of gene regulation and signal transduction. Past studies in our laboratory using congenic mouse strains indicate that one or more genes which map to the H-2 region of chromosome 17 regulate the rate of lung morphogenesis, defined in this context as differentiative heterochrony among strains. Since hormones and growth factors are the messengers of morphogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 65 publications
1
18
1
Order By: Relevance
“…The impact of TNF-alpha on lung branching morphogenesis has not been studied in detail. Early reports suggested that TNF-alpha enhanced embryonic lung branching morphogenesis (Jaskoll et al, 1994). However, numerous studies in both human and animal models have shown a correlation between TNF-alpha and inhibition of lung growth and development.…”
Section: Discussionmentioning
confidence: 98%
“…The impact of TNF-alpha on lung branching morphogenesis has not been studied in detail. Early reports suggested that TNF-alpha enhanced embryonic lung branching morphogenesis (Jaskoll et al, 1994). However, numerous studies in both human and animal models have shown a correlation between TNF-alpha and inhibition of lung growth and development.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously demonstrated that TNF is important to embryonic pulmonary branching morphogenesis (Jaskoll et al, 1994a;Melnick et al, 1996). Thus, we in- vestigated the spatiotemporal distribution of TNF and its two receptors, TNF-R1 and TNF-R2, in the embryonic SMGs.…”
Section: Tnf Il-6 and Cognate Receptorsmentioning
confidence: 99%
“…Given that TGF-␤s have been shown to be an important regulator of embryonic salivary gland morphogenesis in vitro and in vivo (Hardman et al, 1994;Jaskoll et al, 1994a) and that both TGF-␤2 and TGF-␤3 null mice exhibit abnormal lungs (Kaartinen et al, 1995;Sanford et al, 1997), we postulated that TGF-␤2 and/or TGF-␤3 are essential for normal in vivo embryonic salivary gland development. Thus, we evaluated perinatal and neonatal TGF-␤2 and TGF-␤3 null mice.…”
Section: Tgf-␤2 and Tgf-␤3 Null Micementioning
confidence: 99%
See 1 more Smart Citation
“…Organ cultures of embryonic lung rudiments have been used by many investigators to examine control factors involved in lung branching morphogenesis. A number of substances, such as epidermal growth factor, transforming growth factor-,Bl (TGF-,B1), tumor necrosis factor-a, glucocorticoids, platelet derived growth factor, and retinoic acid, have been tested for their effects on lung branching morphogenesis (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). These and other studies illustrate the complexity of lung branching morphogenesis, which may involve growth factors, components of extracellular matrix, matrix-degrading enzymes, and cell-surface molecules (27)(28)(29)(30)(31)(32)(33).…”
mentioning
confidence: 99%